Tunnelling - Megaw, T. M., 1908- (ICE works construction guides., 1982)
The first part of this guide considers the site in terms of organization, safety, surveys and preparation. The second part describes the various common types of tunnel and discusses the appropriate machinery, techniques and operational aspects.